Enfrentamento espiritual perante a pandemia do coronavírus (COVID-19) e suas repercussões no sentido de vida e nos afetos - Marinho, Thayana Maria Olimpio (2021)
The new Coronavirus pandemic (Covid-19) caused many changes in individual and social life, with a change in lifestyle and also in value priorities and, consequently, in the perception of the search and the presence of meanings in life. Taking into account the aforementioned considerations, this dissertation aimed to find out to what extent spiritual coping in the face of the Covid-19 pandemic is associated with the perception of meaning in life and positive and negative affects. The research was carried out using a quantitative methodology, during the year 2020. The Spiritual Coping Scale for the Coronavirus Epidemic (EEPEC) was built as instruments for this study, and administered together with the Meaning of Life Questionnaire (QSV), the Positive and Negative Affects Scale and a Sociodemographic Questionnaire to a sample of 243 people from the Brazilian population. According to a factor analysis administered on the EEPEC scale, six factors emerged, namely: Factor I- Existential Frustration Condition; Factor II- Resilience; Factor III- Fear; Factor IV-Meaning of Meaning; Factor V- Self-transcendence; Factor VI- Forms of Spiritual Coping.First, the correlation of the scale was observed. EEPEC with the degree of presence and search for meaning. The presence of meaning was positively associated with the factors Resilience, Resignification of Meaning, Self-transcendence and Spiritual Coping. While in the search for meaning it was related precisely to the Existential Frustration, Resilience, Fear, Resignification of Meaning and Self-transcendence. Positive Affections correlated directly with Resilience, Resignification of Meaning, Self-transcendence, Spiritual Confrontation and negatively with Existential Frustration. Meanwhile, negative affects were positively associated with Existential Frustration, Fear and negatively with Self-transcendence. The results were discussed in light of Logotherapy and existential analysis.